Implementation Protection of Victims of Violence Against Minors - Mawar Irfa Hani Siregar (International Journal of Students Education, 2024)
This study aim For study implementation protection towards victims of violence child below age. Violence to child is problem seriously threatening well-being physical, emotional, and psychological children. Focus main this study is in steps concrete measures taken by institutions related, like institution protection children, police, and institutions law, for protect victims of violence child. Method used in the article this is literature review, which involves searching, selecting, and analyzing critical to relevant articles, books and reports with topic protection child. Research result show that implementation protection child still faced with various challenges, incl limitations source power, lack of awareness society, and obstacles in enforcement law. However, the findings are also identifying practice best and opportunities for increase effectiveness protection children in the future. Implications policy from this study support necessity collaboration cross sector, increase source power, as well holistic approach in protect children from violence. As for suggestions from results study about protection child below age , for give The results are good and need to be maintained due to, effect law from protection child will impact reduced violence to child below age in accordance with action punishment or witnesses that apply under state law.